Old and new cultural areas of an industrial town on the example of Bytom, Ruda Śląska and Zabrze - Smołka-Franke, Brygida (Studia Etnologiczne i Antropologiczne, 2013)
The aim of the article is to discuss the processes of continuity and change that take place within the space of an industrial town, connected with the functioning of their cultural areas. The subject of interest is the process of creating qualitatively new cultural areas, changes of perception and valorization of socially degraded and empty cultural areas that are being ascribed new functions and meanings, as well as the development, maintenance and proper development of historical cultural areas of an industrial town, constituting the cultural heritage of this category of centres. The phenomenon of changes and valorization, was analysed on the example of the processes taking places in three towns, constituting the composition of the Upper-Silesian aglomeration, namely Bytom, Ruda Śląska and Zabrze.